2019
DOI: 10.3390/nu11020327
|View full text |Cite
|
Sign up to set email alerts
|

Binge-Type Eating in Rats is Facilitated by Neuromedin U Receptor 2 in the Nucleus Accumbens and Ventral Tegmental Area

Abstract: Binge-eating disorder (BED) is the most common eating disorder, characterized by rapid, recurrent overconsumption of highly palatable food in a short time frame. BED shares an overlapping behavioral phenotype with obesity, which is also linked to the overconsumption of highly palatable foods. The reinforcing properties of highly palatable foods are mediated by the nucleus accumbens (NAc) and the ventral tegmental area (VTA), which have been implicated in the overconsumption behavior observed in BED and obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…It is also plausible that the behavioural responses to NMU into the posterior part of the VTA, where rats self‐administer alcohol, may be diverge. Another physiological role of NMU signalling within the aVTA is however most likely as we here show that the aVTA expresses NMU as well as NMUR2 and that NMUR2 was recently detected in the VTA . Indeed, both aVTA and LDTg were identified as novel areas, where NMU acts to reduce 4‐hour chow intake in mice, further confirming its anorexigenic properties .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is also plausible that the behavioural responses to NMU into the posterior part of the VTA, where rats self‐administer alcohol, may be diverge. Another physiological role of NMU signalling within the aVTA is however most likely as we here show that the aVTA expresses NMU as well as NMUR2 and that NMUR2 was recently detected in the VTA . Indeed, both aVTA and LDTg were identified as novel areas, where NMU acts to reduce 4‐hour chow intake in mice, further confirming its anorexigenic properties .…”
Section: Discussionsupporting
confidence: 69%
“…Alcohol‐mediated behaviours are mandated via alcohol's ability to activate the nucleus accumbens (NAc) shell (for review). In addition, this area contains NMU, the expression of NMUR2 has been identified on GABA terminals in NAc, and the NMUR2 protein has been detected within NAc . We therefore hypothesise that activation of NMUR2 in NAc shell attenuates acute, as well as chronic effects of alcohol in rodents.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, incubation of sucrose craving was not associated with changes in cortical (prelimbic, infralimbic, orbitofrontal) perineuronal net densities (Slaker, Barnes, Sorg, & Grimm, 2016). Neuromedin is a neuropeptide involved in many behaviors, including feeding (Smith, Kasper, Ara, Anastasio, & Hommel, 2019;Vallöf, Kalafateli, & Jerlhag, 2019). In contrast to these negative effects, using a molecular manipulation, McCue et al (2019) reported that knockdown of neuromedin U receptor 2 in the paraventricular nucleus of the hypothalamus prevents incubation of high-fat food craving.…”
Section: Molecular Studiesmentioning
confidence: 98%
“…In contrast to these negative effects, using a molecular manipulation, McCue et al (2019) reported that knockdown of neuromedin U receptor 2 in the paraventricular nucleus of the hypothalamus prevents incubation of high-fat food craving. Neuromedin is a neuropeptide involved in many behaviors, including feeding (Smith, Kasper, Ara, Anastasio, & Hommel, 2019;Vallöf, Kalafateli, & Jerlhag, 2019). Fig.…”
Section: Molecular Studiesmentioning
confidence: 99%